Epigenetics, Nutrition, Disease and Drug Development - Lundstrom, Kenneth (Current Drug Discovery Technologies, 2019)
Epigenetic mechanisms comprising of DNA methylation, histone modifications and gene silencing by RNA interference have been strongly linked to the development and progression of various diseases. These findings have triggered research on epigenetic functions and signal pathways as targets for novel drug discovery. Dietary intake has also presented significant influence on human health and disease development and nutritional modifications have proven important in prevention, but also the treatment of disease. Moreover, a strong link between nutrition and epigenetic changes has been established. Therefore, in attempts to develop novel safer and more efficacious drugs, both nutritional requirements and epigenetic mechanisms need to be addressed.
Keywords: nutrition